Vendor Managed Inventory: Why you need to talk to your supplier - Frederik Zachariassen; Henning de Haas; Sirle Bürkland (Journal of Industrial Engineering and Management, 2014)
Purpose The purpose of this paper is to investigate the concept of Vendor Managed Inventory (VMI) from an inter-organisational perspective. Extant literature on VMI tends to investigate the concept from a focal perspective, even though VMI has originally been born as a collaborative arrangement. Design/methodology/approach The paper is based on a literature review and an empirical study. It provides a comprehensive literature review on VMI and an illustrative case study of a supplier and a buyer jointly implementing VMI. Findings The findings of this paper are twofold. First, a literature review uncovers that contemporary research has delimited the analysis of VMI to a focal company perspective as current VMI cost models tend not to capture the picture of the complete supply chain. Second, it demonstrates through an illustrative case study that adoption of an inter-organisational approach to VMI is vital if companies are to optimize their buyer-supplier relationships. Research limitations/implications Future research should test the implications proposed in the empirical section, as this piece of research can be seen as exploratory case study research with the aim of analytical generalizations. Practical implications The inter-organisational VMI cost perspective in supply chains should be emphasized in purchasing departments since such a perspective significantly raises the awareness of the costs incurred in a supply chain. Originality/value Existing research has not explicitly focused on inter-organisational costs incurred by companies implementing VMI. This study seeks to bridge this research gap.